Safeguarding critical e-documents : implementing a program for securing confidential information assets - Smallwood, Robert F., 1959- (John Wiley & Sons, Inc., 2012)
"Practical, step-by-step guidance for corporations, universities and government agencies to protect and secure confidential documents and business records. Managers and public officials are looking for technology and information governance solutions to "information leakage" in an understandable, concise format. Safeguarding Critical E-Documents provides a road map for corporations, governments, financial services firms, hospitals, law firms, universities and other organizations to safeguard their internal electronic documents and private communications. Provides practical, step-by-step guidance on protecting sensitive and confidential documents--even if they leave the organization electronically or on portable devices Presents a blueprint for corporations, governments, financial services firms, hospitals, law firms, universities and other organizations to safeguard internal electronic documents and private communications Offers a concise format for securing your organizations from information leakage In light of the recent WikiLeaks revelations, governments and businesses have heightened awareness of the vulnerability of confidential internal documents and communications. Timely and relevant, Safeguarding Critical E-Documents shows how to keep internal documents from getting into the wrong hands and weakening your competitive position, or possible damaging your organization's reputation and leading to costly investigations"--